Preparation method of aluminum nitride whisker and high-strength and high-thermal-conductivity ceramic substrate

The sintering of aluminum nitride whiskers prepared by the rapid nitriding method and spherical aluminum nitride has solved the problem of difficulty in rapid synthesis of high-strength and high-thermal conductivity ceramic substrates in the prior art, and achieved an efficient and low-cost preparation method.

CN119392346APending Publication Date: 2025-02-07HUAZHONG UNIV OF SCI & TECH
View PDF 0 Cites 4 Cited by

Patent Information

Application Number
CN202411510432.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

It is difficult to quickly synthesize high-strength, high-thermal conductivity aluminum nitride ceramic substrates in the prior art, and a large number of reinforcement and sintering aids are often required, which is costly.

Method used

Aluminum nitride whiskers with uniform morphology and aspect ratios were prepared by rapid nitriding method, and sintered with spherical aluminum nitride without additional sintering aids and reinforcers only using aluminum nitride whiskers as additives, without additional sintering agents and reinforcers. , prepare high-strength and high-thermal conductivity aluminum nitride ceramic substrates.

Benefits of technology

The preparation of high-strength and high-thermal conductivity aluminum nitride ceramic substrates is achieved, reducing costs and energy consumption, and no additional additives are required, suitable for commercial mass production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119392346A_ABST
    Figure CN119392346A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of whisker material growth and ceramic substrate preparation, and discloses a preparation method of an aluminum nitride whisker and a high-strength and high-thermal-conductivity ceramic substrate, and the preparation method of the aluminum nitride whisker comprises the following steps: mixing aluminum powder serving as a raw material and ammonium salt serving as an inducer according to a mass ratio of (2: 1)-(1: 2); and carrying out heat preservation for 0.5-2 hours at the temperature of 800-1100 DEG C under the nitrogen and / or ammonia atmosphere condition, and carrying out nitridation reaction. According to the invention, a whisker and ceramic substrate synthesis method is improved, aluminum nitride whiskers with uniform morphology and length-diameter ratio are controllably synthesized through a rapid nitriding method, and the aluminum nitride whiskers and spherical aluminum nitride are sintered only by taking the aluminum nitride whiskers as an additive without the participation of additional sintering aids and reinforcers, so that the ceramic substrate is obtained. The high-strength and high-thermal-conductivity aluminum nitride ceramic substrate is obtained and has high mechanical strength and thermal conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of whisker material growth and ceramic substrate preparation, and more specifically, relates to a preparation method of aluminum nitride whiskers and a high-strength and high-thermal-conductivity ceramic substrate. Background Art

[0002] Aluminum nitride (AlN) is an advanced semiconductor ceramic material, composed of Al and N atoms covalently bonded into a tetrahedral structure [AlN4]. AlN generally belongs to the hexagonal system (h-AlN), with lattice constants a=b=0.311nm, c=0.498nm, a wurtzite structure, and a theoretical density of 3.26g / cm 3 h-AlN has good comprehensive physical and chemical properties, including extremely high thermal conductivity (70-210 W / m·K for polycrystalline blocks and 270-320 W / m·K for single crystals), low thermal expansion coefficient (4.5×10 -6 / K), and Si(4×10 -6 / K) and SiC (4.7×10 -6 / K) with good matching and excellent electrical properties (dielectric strength can reach 20kV / mm, 1MHz dielectric loss is less than 5×10 -4 , volume resistivity can reach 10 10 Ω·cm or more) and resistant to molten salt corrosion, non-toxic, etc. In view of the above advantages, AlN has gradually attracted the attention of many researchers at home and abroad. It is considered to be an ideal substrate material for third-generation semiconductor (SiC, GaN-based) integrated circuits and high-frequency power modules (such as IGBT, MOSFET), and has great application prospects in new energy vehicles, photovoltaic power generation arrays, ultra-high-speed railways and other fields.

[0003] However, with the substantial increase in chip integration and computing power, high power density and high switching frequency have become an inevitable trend in the development of electronic devices, which has put forward higher requirements for electronic packaging materials. In order to adapt to the inevitable thermal shock and stress changes of power modules during high-frequency switching, the AlN substrate used must have high thermal conductivity and high mechanical strength to ensure the service life of the equipment.

[0004] At present, there are many technical paths for the synthesis of AlN. The direct nitridation method and carbon thermal reduction method are mainly used in industry, while some laboratories use high-energy ball milling, chemical vapor deposition, sol-gel, arc melting and microwave synthesis. Among them, the direct nitridation method has a simple process and low cost, but there are problems such as low conversion rate and easy agglomeration of reaction products; the carbon thermal reduction method has high product purity, but requires high temperature and long-term reaction, and the tail gas needs special treatment, which is costly; the laboratory method can be customized for synthesis, but there are generally problems such as low yield and difficulty in amplification. Although industrial development in recent years has basically achieved the commercial production of spherical AlN, there is still a lack of controllable processes for the rapid synthesis of AlN whiskers, which limits the application of AlN substrates under high load conditions. At present, the growth of AlN whiskers (the diameter of the whiskers is nanometers and the length is 1 to 10 μm) often requires the participation of catalysts (such as iron nitrate or iron powder) and reactions at high temperatures (above 1200°C) to generate.

[0005] At the same time, in order to achieve performance indicators such as high strength and high thermal conductivity, commercial AlN substrates often add a large proportion of reinforcing agents (>10wt%) and sintering aids (2-5wt%), as well as a certain amount of plasticizers, adhesives and dispersants. After pre-forming by casting and cold isostatic pressing (100-300MPa), they are sintered at high temperature at 1800-2200℃ for 2-6h, or sintered at 1600-1700℃ for 8-10h. There is an urgent need to seek low-cost and high-efficiency technical approaches to prepare high-strength and high-thermal conductivity AlN ceramic substrates. Summary of the invention

[0006] In view of the above defects or improvement needs of the prior art, the purpose of the present invention is to provide a method for preparing aluminum nitride whiskers and high-strength, high-thermal-conductivity ceramic substrates, wherein the whisker and ceramic substrate synthesis method is improved, and aluminum nitride whiskers with uniform morphology and aspect ratio are controllably synthesized by rapid nitridation, and the aluminum nitride whiskers are sintered with spherical aluminum nitride without the participation of additional sintering aids and reinforcing agents, and the aluminum nitride whiskers are used as additives to obtain a high-strength, high-thermal-conductivity aluminum nitride ceramic substrate with high mechanical strength and thermal conductivity. In the preparation process of the ceramic substrate, the aluminum nitride whiskers have a "one-dose, two-effect" effect. Only a small amount of aluminum nitride whiskers are added, which can be used as a sintering aid and a reinforcing agent at the same time. Without the need for additional sintering aids and reinforcing agents, the sintering performance of the aluminum nitride powder can be greatly improved, thereby obtaining a high-strength, high-thermal-conductivity aluminum nitride ceramic substrate.

[0007] To achieve the above object, according to one aspect of the present invention, a method for preparing aluminum nitride whiskers is provided, characterized in that the preparation method is to use aluminum powder as a raw material and ammonium salt as an inducer, mix the aluminum powder and the inducer in a mass ratio of 2:1 to 1:2, and then carry out a nitridation reaction at a temperature of 800 to 1100°C for 0.5 to 2h in a nitrogen and / or ammonia atmosphere.

[0008] As a further preferred embodiment of the present invention, the mass ratio of aluminum powder to inducer is 1:1, and the nitridation reaction is carried out at a temperature of 1000° C. for 1 hour.

[0009] As a further preferred embodiment of the present invention, the inducing agent is one or a mixture of NH4HCO3, (NH4)2CO3, NH4Cl, NH4NO3; preferably, the purity of the inducing agent is analytical grade;

[0010] Preferably, the aluminum powder has an average particle size (d 50 ) is a spherical aluminum powder of 5 to 6 μm;

[0011] The heating rate of the nitridation reaction is 10-20°C / min.

[0012] As a further preferred embodiment of the present invention, the mixing of the aluminum powder and the inducer is carried out under the protection of a protective gas, wherein the protective gas includes nitrogen or argon; and the mixing method is a mechanical oscillation method.

[0013] As a further preferred embodiment of the present invention, after the nitridation reaction is completed, the cooled product is further subjected to a grinding treatment; the grinding treatment is performed under the protection of a protective gas, and the protective gas includes nitrogen or argon.

[0014] According to another aspect of the present invention, the present invention provides a method for preparing a high-strength and high-thermal-conductivity aluminum nitride ceramic substrate, characterized in that the preparation method uses aluminum nitride whiskers as additives, adds the aluminum nitride whiskers to spherical aluminum nitride powder, cold presses and shapes the powder, and then performs hot pressing and sintering, without the participation of other sintering aids and strengthening agents, to obtain a high-strength and high-thermal-conductivity aluminum nitride ceramic substrate;

[0015] The aluminum nitride whiskers account for 2 to 8 wt % of the mixture of the aluminum nitride whiskers and the spherical aluminum nitride powder.

[0016] As a further preferred embodiment of the present invention, the aluminum nitride whiskers are added to the spherical aluminum nitride powder and mixed evenly under a protective gas environment;

[0017] The pressure applied by the cold pressing is 5 to 15 MPa;

[0018] The hot pressing sintering temperature is 1600-1700°C, the pressure is 30-50MPa, and the sintering time is 10-30min;

[0019] Preferably, the average particle size (d 50 ) is 1 to 3 μm.

[0020] According to another aspect of the present invention, the present invention provides a high-strength, high-thermal-conductivity aluminum nitride ceramic substrate made by the above-mentioned preparation method.

[0021] As a further preferred embodiment of the present invention, the bending strength of the aluminum nitride ceramic substrate is not less than 402.3 MPa, the thermal conductivity is not less than 112.2 W / m·K, and the fracture toughness is not less than 3.19 MPa·m 1 / 2 .

[0022] According to another aspect of the present invention, the present invention provides the use of the above aluminum nitride ceramic substrate as a packaging material in a power semiconductor device.

[0023] Compared with the prior art, the above technical solutions conceived by the present invention can achieve the following

[0024] Beneficial effects:

[0025] 1. The present invention adopts a rapid nitridation method to prepare aluminum nitride whiskers, which is simple, convenient, and low-cost. AlN whiskers can be obtained without additional AlN seed crystals; the synthesis temperature can be as low as 800-1100°C (especially high-purity AlN whiskers can be obtained at 1000°C); the morphology and aspect ratio are uniform (the whisker diameter is nanometer-level and the length is 1-10 μm), and the dispersibility is good; the batch repeatability is good, and it is suitable for commercial mass production.

[0026] 2. The present invention also proposes to utilize the "one dose, two effects" effect of aluminum nitride whiskers, that is, without the need for additional additives and sintering aids, only a small amount of aluminum nitride whiskers need to be introduced to improve the sintering performance of spherical aluminum nitride, thereby obtaining a high-strength, high-thermal-conductivity aluminum nitride ceramic substrate. Thanks to the high specific surface area of ​​aluminum nitride whiskers, the activation energy required for ceramic sintering is reduced, and small grains are more likely to devour each other and merge to form large grains, thereby improving the sintering performance; the sintering temperature for preparing the aluminum nitride ceramic substrate of the present invention can be set to 1600-1700°C. Due to the lower sintering temperature (≤1700°C), not all aluminum nitride whiskers act as "sintering aids" at this time, and the remaining aluminum nitride whiskers remain at the grain boundaries, thereby acting as "reinforcers" to improve the mechanical strength of the ceramic. Therefore, the preparation method of the aluminum nitride ceramic substrate in the present invention can overcome the problems of high thermal conductivity and low mechanical properties that are common in existing literature. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 : is a comparison of micrographs of the ground samples prepared in Examples 1 to 4 at different magnifications, wherein: Figure 1 (a1) and (a2) correspond to the products of Example 1, Figure 1 (b1) and (b2) correspond to the products of Example 2, Figure 1(c1) and (c2) correspond to the products of Example 3, Figure 1 (d1) and (d2) correspond to the products of Example 4. And, Figure 1 (a1), (b1), (c1), and (d1) have the same magnification, and the scale bars represent 5 μm; Figure 1 (a2), (b2), (c2), and (d2) have the same magnification, and the scale bars all represent 1 μm.

[0028] Figure 2 : is a comparison of micrographs of the ground samples prepared in Examples 5 to 8 at different magnifications, wherein: Figure 2 (a1) and (a2) correspond to the products of Example 5, Figure 2 (b1) and (b2) correspond to the products of Example 6, Figure 2 (c1) and (c2) correspond to the products of Example 7, Figure 2 (d1) and (d2) correspond to the products of Example 8. And, Figure 2 (a1), (b1), (c1), and (d1) have the same magnification, and the scale bars represent 5 μm; Figure 2 (a2), (b2), (c2), and (d2) have the same magnification, and the scale bars all represent 1 μm.

[0029] Figure 3 : is a comparison of micrographs of the ground samples prepared in Examples 9 to 11 at different magnifications, wherein: Figure 3 (a1) and (a2) correspond to the products of Example 9, Figure 3 (b1) and (b2) correspond to the products of Example 10, Figure 3 (c1) and (c2) correspond to the products of Example 11. And, Figure 3 (a1), (b1), and (c1) have the same magnification, and the scale bars represent 5 μm; Figure 3 (a2), (b2), and (c2) have the same magnification, and the scale bars all represent 1 μm.

[0030] Figure 4 is the X-ray diffraction (XRD) pattern of the ground sample prepared in Example 10.

[0031] Figure 5 is a comparison of cross-sectional micrographs of the samples prepared in Examples 12 to 15 at the same magnification, wherein: Figure 5 (a) corresponds to the product of Example 12, Figure 5 (b) corresponds to the product of Example 13, Figure 5 (c) corresponds to the product of Example 14, Figure 5(d) corresponds to the product of Example 15. The scale bars in the figures all represent 2 μm.

[0032] Figure 6 The cross-sectional micrographs of the samples prepared in Comparative Examples 1 to 3 at different magnifications are compared, wherein: Figure 6 (a1), (a2), and (a3) ​​correspond to the product of Example 1, Figure 6 (b1), (b2), and (b3) correspond to the products of Example 2, Figure 6 (c1), (c2), and (c3) correspond to the products of Example 3. And, Figure 6 (a1), (b1), and (c1) have the same magnification, and the scale bars represent 5 μm; Figure 6 (a2), (b2), and (c2) have the same magnification, and the scale bars represent 2 μm; Figure 6 (a3), (b3), and (c3) have the same magnification, and the scale bars all represent 1 μm. DETAILED DESCRIPTION

[0033] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0034] Example 1

[0035] (1) Spherical aluminum powder with an average particle size of 5 to 6 μm and NH4Cl induction agent (analytical grade, the same below) were ground and mixed in an inert gas environment (argon was used in this embodiment and the following embodiments) at a mass ratio of 4:1, placed in a covered graphite crucible, transferred to a tube furnace for evacuation, and passed nitrogen protection;

[0036] (2) Adjust the nitrogen flow rate in the tube furnace to 100 mL / min, set the heating rate to 10 °C / min, raise the temperature to 800 °C for nitridation reaction, and keep it at this temperature for 4 h;

[0037] (3) After cooling in the furnace, take out the obtained powder, grind it in an inert environment, and seal it for later use.

[0038] Example 2

[0039] (1) Spherical aluminum powder with an average particle size of 5 to 6 μm and NH4Cl inducer are ground and mixed in an inert gas environment at a ratio of 2:1 (mass ratio, the same below), placed in a graphite crucible with a lid, transferred to a tube furnace for evacuation, and protected by nitrogen;

[0040] (2) Adjust the nitrogen flow rate in the tube furnace to 100 mL / min, set the heating rate to 10 °C / min, raise the temperature to 800 °C for nitridation reaction, and keep it at this temperature for 4 h;

[0041] (3) After cooling in the furnace, take out the obtained powder, grind it in an inert environment, and seal it for later use.

[0042] Example 3

[0043] (1) Spherical aluminum powder with an average particle size of 5 to 6 μm and NH4Cl inducer are ground and mixed in an inert gas environment at a ratio of 1:1, placed in a graphite crucible with a cover, transferred to a tube furnace for evacuation, and protected by nitrogen;

[0044] (2) Adjust the nitrogen flow rate in the tube furnace to 100 mL / min, set the heating rate to 10 °C / min, raise the temperature to 800 °C for nitridation reaction, and keep it at this temperature for 4 h;

[0045] (3) After cooling in the furnace, take out the obtained powder, grind it in an inert environment, and seal it for later use.

[0046] Example 4

[0047] (1) Spherical aluminum powder with an average particle size of 5 to 6 μm and NH4Cl inducer are ground and mixed in an inert gas environment at a ratio of 1:2, placed in a graphite crucible with a cover, transferred to a tube furnace for evacuation, and protected by nitrogen;

[0048] (2) Adjust the nitrogen flow rate in the tube furnace to 100 mL / min, set the heating rate to 10 °C / min, raise the temperature to 800 °C for nitridation reaction, and keep it at this temperature for 4 h;

[0049] (3) After cooling in the furnace, take out the obtained powder, grind it in an inert environment, and seal it for later use.

[0050] The micrographs of the samples prepared in Examples 1 to 4 are as follows: Figure 1 As shown, it is not difficult to see that under different aluminum powder and NH4Cl mass ratio conditions, as the proportion of NH4Cl added gradually increases, the length of the whiskers formed on the surface of the spherical aluminum powder gradually increases, and a large number of whiskers extend from the outside to the inside of the complete sphere. When NH4Cl is less (such as Example 1), the elongation induction effect on the whiskers is weak; when the mass ratio of NH4Cl to spherical aluminum powder increases to 1:1, the whiskers have a suitable aspect ratio and morphology; and when NH4Cl is more, the whisker length is further extended.

[0051] Example 5

[0052] (1) Spherical aluminum powder with an average particle size of 5 to 6 μm and NH4Cl inducer are ground and mixed in an inert gas environment at a mass ratio of 1:1, placed in a covered graphite crucible, transferred to a tube furnace for evacuation, and protected by nitrogen;

[0053] (2) Adjust the nitrogen flow rate in the tube furnace to 500 mL / min, set the heating rate to 15 °C / min, raise the temperature to 800 °C for nitridation reaction, and keep it at this temperature for 2 h;

[0054] (3) After cooling in the furnace, take out the obtained powder, grind it in an inert environment, and seal it for later use.

[0055] Example 6

[0056] (1) Spherical aluminum powder with an average particle size of 5 to 6 μm and NH4Cl inducer are ground and mixed in an inert gas environment at a mass ratio of 1:1, placed in a covered graphite crucible, transferred to a tube furnace for evacuation, and protected by nitrogen;

[0057] (2) Adjust the nitrogen flow rate in the tube furnace to 500 mL / min, set the heating rate to 15 °C / min, raise the temperature to 900 °C for nitridation reaction, and keep it at this temperature for 2 h;

[0058] (3) After cooling in the furnace, take out the obtained powder, grind it in an inert environment, and seal it for later use.

[0059] Example 7

[0060] (1) Spherical aluminum powder with an average particle size of 5 to 6 μm and NH4Cl inducer are ground and mixed in an inert gas environment at a mass ratio of 1:1, placed in a covered graphite crucible, transferred to a tube furnace for evacuation, and protected by nitrogen;

[0061] (2) Adjust the nitrogen flow rate in the tube furnace to 500 mL / min, set the heating rate to 15 °C / min, raise the temperature to 1000 °C for nitridation reaction, and keep it at this temperature for 2 h;

[0062] (3) After cooling in the furnace, take out the obtained powder, grind it in an inert environment, and seal it for later use.

[0063] Example 8

[0064] (1) Spherical aluminum powder with an average particle size of 5 to 6 μm and NH4Cl inducer are ground and mixed in an inert gas environment at a mass ratio of 1:1, placed in a covered graphite crucible, transferred to a tube furnace for evacuation, and protected by nitrogen;

[0065] (2) Adjust the nitrogen flow rate in the tube furnace to 500 mL / min, set the heating rate to 15 °C / min, raise the temperature to 1100 °C for nitridation reaction, and keep it at this temperature for 2 h;

[0066] (3) After cooling in the furnace, take out the obtained powder, grind it in an inert environment, and seal it for later use.

[0067] Microscopic photographs of the samples prepared in Examples 5 to 8 are shown in FIG. Figure 2 As shown in the figure, it is not difficult to see that under different nitriding reaction temperature conditions, as the reaction temperature gradually increases, the degree of nitriding reaction on the surface of spherical aluminum powder gradually deepens, and the complete sphere gradually breaks into columnar seed crystals for whisker growth. At 800°C, whiskers begin to form on the surface of spherical aluminum powder; at 900°C, a large number of whiskers are generated on the surface of spherical aluminum powder; at 1000°C, the sphere is broken, and a large number of whiskers are also generated inside the spherical aluminum powder; at 1100°C, whiskers are further generated in large quantities.

[0068] Example 9

[0069] (1) Spherical aluminum powder with an average particle size of 5 to 6 μm and NH4Cl inducer are ground and mixed in an inert gas environment at a mass ratio of 1:1, placed in a covered graphite crucible, transferred to a tube furnace for evacuation, and protected by nitrogen;

[0070] (2) Adjust the nitrogen flow rate in the tube furnace to 500 mL / min, set the heating rate to 20 °C / min, raise the temperature to 1000 °C for nitridation reaction, and keep it at this temperature for 0.5 h;

[0071] (3) After cooling in the furnace, take out the obtained powder, grind it in an inert environment, and seal it for later use.

[0072] Example 10

[0073] (1) Spherical aluminum powder with an average particle size of 5 to 6 μm and NH4Cl inducer are ground and mixed in an inert gas environment at a mass ratio of 1:1, placed in a covered graphite crucible, transferred to a tube furnace for evacuation, and protected by nitrogen;

[0074] (2) Adjust the nitrogen flow rate in the tube furnace to 500 mL / min, set the heating rate to 20 °C / min, raise the temperature to 1000 °C for nitridation reaction, and keep it at this temperature for 1 h;

[0075] (3) After cooling in the furnace, take out the obtained powder, grind it in an inert environment, and seal it for later use.

[0076] Embodiment 11

[0077] (1) Spherical aluminum powder with an average particle size of 5 to 6 μm and NH4Cl inducer are ground and mixed in an inert gas environment at a mass ratio of 1:1, placed in a covered graphite crucible, transferred to a tube furnace for evacuation, and protected by nitrogen;

[0078] (2) Adjust the nitrogen flow rate in the tube furnace to 500 mL / min, set the heating rate to 20 °C / min, raise the temperature to 1000 °C for nitridation reaction, and keep it at this temperature for 2 h;

[0079] (3) After cooling in the furnace, take out the obtained powder, grind it in an inert environment, and seal it for later use.

[0080] Microscopic photographs of the samples prepared in Examples 9 to 11 are shown in FIG. Figure 3 As shown, it is not difficult to see that when the required nitriding temperature (i.e., 1000°C) is reached, whiskers can be generated under different holding times. Of course, when the holding time is 1h, the whisker morphology and aspect ratio are the best. The XRD spectrum of the sample prepared in Example 10 is shown in Figure 4 As shown, it is not difficult to see that the diffraction peak position of the obtained product corresponds to the standard diffraction peak position of hexagonal aluminum nitride (h-AlN), indicating that the synthesized product is completely h-AlN.

[0081] On the other hand, regarding the preparation process of high-strength and high-thermal-conductivity aluminum nitride ceramic substrates, there are the following examples and comparative examples (the "spherical aluminum nitride" that appears later is commercial aluminum nitride powder purchased from Ningxia Aisenda, and the microscopic morphology is the average particle size (d 50 ) is spherical with a diameter of 1 to 3 μm):

[0082] Example 12

[0083] The specific process steps for hot pressing sintering of aluminum nitride ceramic substrates are as follows:

[0084] (1) in an inert gas environment (i.e., argon), commercial spherical aluminum nitride and aluminum nitride whiskers prepared under preferred conditions (i.e., the product of Example 10) were uniformly mixed, the amount of the aluminum nitride whiskers added was controlled to be 2 wt %, and the mixture was placed in a graphite mold for later use;

[0085] (2) The mold containing the mixed aluminum nitride powder was pre-pressed and fixed in a cold press at a pressure of 10 MPa, and the outer layer of the mold was wrapped with 5 mm of thermal insulation carbon felt;

[0086] (3) The graphite mold is placed in a hot pressing sintering furnace, and the hot pressing pressure is set to 40 MPa, the sintering temperature is set to 1700°C, and the sintering time is set to 10 min. After the sintering is completed, the sample is cooled and taken out, and the desired aluminum nitride ceramic substrate is obtained after surface polishing.

[0087] Embodiment 13

[0088] (1) Commercial spherical aluminum nitride and aluminum nitride whiskers (product of Example 10) were mixed uniformly in an argon environment, and the addition amount of the aluminum nitride whiskers was controlled to be 4 wt %, and placed in a graphite mold for standby use;

[0089] (2) The mold containing the mixed aluminum nitride powder was pre-pressed and fixed in a cold press at a pressure of 10 MPa, and the outer layer of the mold was wrapped with 5 mm of thermal insulation carbon felt;

[0090] (3) Place the graphite mold in a hot pressing sintering furnace, set the hot pressing pressure to 40 MPa, the sintering temperature to 1700°C, and the sintering time to 10 min. After sintering, cool and take out the sample, and polish the surface to obtain the sample.

[0091] Embodiment 14

[0092] (1) Commercial spherical aluminum nitride and aluminum nitride whiskers (product of Example 10) were mixed uniformly in an argon environment, and the addition amount of the aluminum nitride whiskers was controlled to be 6 wt %, and placed in a graphite mold for standby use;

[0093] (2) The mold containing the mixed aluminum nitride powder was pre-pressed and fixed in a cold press at a pressure of 10 MPa, and the outer layer of the mold was wrapped with 5 mm of thermal insulation carbon felt;

[0094] (3) Place the graphite mold in a hot pressing sintering furnace, set the hot pressing pressure to 40 MPa, the sintering temperature to 1700°C, and the sintering time to 10 min. After sintering, cool and take out the sample, and polish the surface to obtain the sample.

[0095] Embodiment 15

[0096] (1) in an argon environment, commercial spherical aluminum nitride and aluminum nitride whiskers (product of Example 10) were mixed uniformly, the addition amount of the aluminum nitride whiskers was controlled to be 8 wt %, and the mixture was placed in a graphite mold for later use;

[0097] (2) The mold containing the mixed aluminum nitride powder was pre-pressed and fixed in a cold press at a pressure of 10 MPa, and the outer layer of the mold was wrapped with 5 mm of thermal insulation carbon felt;

[0098] (3) Place the graphite mold in a hot pressing sintering furnace, set the hot pressing pressure to 40 MPa, the sintering temperature to 1700°C, and the sintering time to 10 min. After sintering, cool and take out the sample, and polish the surface to obtain the sample.

[0099] Comparative Example 1

[0100] (1) weighing commercial spherical aluminum nitride powder in an argon environment and placing it in a graphite mold for later use;

[0101] (2) The mold filled with aluminum nitride powder was pre-pressed and fixed in a cold press at a pressure of 10 MPa, and the outer layer of the mold was wrapped with 3 mm insulating carbon felt;

[0102] (3) Place the graphite mold in a hot pressing sintering furnace, set the hot pressing pressure to 40 MPa, the sintering temperature to 1600°C, and the sintering time to 30 min. After sintering, cool and take out the sample, and polish the surface to obtain the sample.

[0103] Comparative Example 2

[0104] (1) weighing commercial spherical aluminum nitride powder in an argon environment and placing it in a graphite mold for later use;

[0105] (2) The mold filled with aluminum nitride powder was pre-pressed and fixed in a cold press at a pressure of 10 MPa, and the outer layer of the mold was wrapped with 4 mm insulating carbon felt;

[0106] (3) Place the graphite mold in a hot pressing sintering furnace, set the hot pressing pressure to 40 MPa, the sintering temperature to 1650°C, and the sintering time to 20 min. After sintering, cool and take out the sample, and polish the surface to obtain the sample.

[0107] Comparative Example 3

[0108] (1) weighing commercial spherical aluminum nitride powder in an argon environment and placing it in a graphite mold for later use;

[0109] (2) The mold filled with aluminum nitride powder was pre-pressed and fixed in a cold press at a pressure of 10 MPa, and the outer layer of the mold was wrapped with 5 mm of thermal insulation carbon felt;

[0110] (3) Place the graphite mold in a hot pressing sintering furnace, set the hot pressing pressure to 40 MPa, the sintering temperature to 1700°C, and the sintering time to 10 min. After sintering, cool and take out the sample, and polish the surface to obtain the sample.

[0111] Comparative Example 4

[0112] (1) weighing the preferred aluminum nitride whisker (i.e., Example 10) in an argon environment and placing it in a graphite mold for later use;

[0113] (2) The mold containing aluminum nitride whiskers was pre-pressed and fixed in a cold press at a pressure of 10 MPa, and the outer layer of the mold was wrapped with 5 mm of thermal insulation carbon felt;

[0114] (3) Place the graphite mold in a hot pressing sintering furnace, set the hot pressing pressure to 40 MPa, the sintering temperature to 1700°C, and the sintering time to 10 min. After sintering, cool and take out the sample, and polish the surface to obtain the sample.

[0115] The cross-sectional micrographs of the aluminum nitride ceramics prepared in Examples 12 to 15 are as follows: Figure 5 As shown, it is not difficult to see that when the addition amount of aluminum nitride whiskers is 2wt%, the sintering performance of the sample is better, that is, there is no obvious pore. As the addition amount of aluminum nitride whiskers increases, the number of whiskers distributed at the grain boundaries increases, and the pores appearing after sintering tend to increase.

[0116] The ceramic substrate obtained by hot pressing and sintering can be processed in a conventional manner, and after the substrate surface is polished, it can be cut into samples by laser to test the three-point bending strength, thermal conductivity and other properties. The performance test results of the aluminum nitride ceramics prepared in Examples 12 to 15 and Comparative Examples 1 to 3 are shown in Table 1.

[0117] Table 1

[0118]

[0119] In Example 12, Example 13, Example 14, Example 15, Comparative Example 3, and Comparative Example 4, the process parameter conditions of step (2) and step (3) are all set the same, and the only difference is that the raw materials used in step (1) are different; it is not difficult to see from Table 1 that compared with using only commercial spherical aluminum nitride as a raw material, or using aluminum nitride whiskers as a raw material, using both commercial spherical aluminum nitride and aluminum nitride whiskers as raw materials, the corresponding products have better bending strength and fracture toughness (while also having the characteristics of high thermal conductivity); it can be seen that commercial spherical aluminum nitride and aluminum nitride whiskers produce a synergistic effect.

[0120] The above embodiments are only examples. For example, when aluminum nitride whiskers are synthesized in one step by the rapid nitridation method, the inducing agent can also be other ammonium salts (analytical grade), such as one or more of NH4HCO3, (NH4)2CO3, NH4Cl, and NH4NO3. For another example, in addition to graphite, the crucible can also use boron nitride, aluminum nitride, etc. The aluminum nitride whiskers used to prepare the aluminum nitride ceramic substrate in Examples 12 to 15 are not limited to the aluminum nitride whiskers obtained by the preparation method of the present invention, but can also be aluminum nitride whiskers obtained by other methods (such as commercially available aluminum nitride whiskers, etc.), all of which can play a "one dose, two effects" role without the need for additional sintering aids and reinforcing agents. In addition, the aluminum nitride whiskers synthesized by the present invention can be placed in an inert gas environment (nitrogen or argon) for long-term storage, and then unsealed for use when needed.

[0121] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing aluminum nitride whiskers, characterized in that: The preparation method comprises the following steps: using aluminum powder as a raw material and ammonium salt as an inducer, mixing the aluminum powder and the inducer in a mass ratio of 2:1 to 1:2, and then performing a nitridation reaction under nitrogen and / or ammonia atmosphere at a temperature of 800 to 1100° C. for 0.5 to 2 hours.

2. The preparation method according to claim 1, characterized in that: The mass ratio of aluminum powder to inducer is 1:1, and the nitridation reaction is carried out at a temperature of 1000°C for 1 hour.

3. The preparation method according to claim 1, characterized in that: The inducing agent is one or a mixture of NH4HCO3, (NH4)2CO3, NH4Cl, NH4NO3; preferably, the purity of the inducing agent is analytical grade; Preferably, the aluminum powder has an average particle size (d 50 ) is a spherical aluminum powder of 5 to 6 μm; The heating rate of the nitridation reaction is 10-20°C / min.

4. The preparation method according to claim 1, characterized in that: The mixing of the aluminum powder and the inducer is carried out under the protection of a protective gas, wherein the protective gas includes nitrogen or argon; the mixing method is a mechanical oscillation method.

5. The preparation method according to claim 1, characterized in that: After the nitridation reaction is completed, the cooled product is further subjected to a grinding treatment; the grinding treatment is performed under the protection of a protective gas, and the protective gas includes nitrogen or argon.

6. A method for preparing a high-strength and high-thermal-conductivity aluminum nitride ceramic substrate, characterized in that: The preparation method uses aluminum nitride whiskers as additives, adds the aluminum nitride whiskers to spherical aluminum nitride powder, performs cold pressing to shape, and then performs hot pressing sintering, without the participation of other sintering aids and strengthening agents, to obtain a high-strength and high-thermal-conductivity aluminum nitride ceramic substrate; The aluminum nitride whiskers account for 2 to 8 wt % of the mixture of the aluminum nitride whiskers and the spherical aluminum nitride powder.

7. The preparation method according to claim 6, characterized in that: adding the aluminum nitride whiskers to the spherical aluminum nitride powder and mixing them uniformly under a protective gas environment; The pressure applied by the cold pressing is 5 to 15 MPa; The hot pressing sintering temperature is 1600-1700°C, the pressure is 30-50MPa, and the sintering time is 10-30min; Preferably, the average particle size (d 50 ) is 1 to 3 μm.

8. A high-strength and high-thermal-conductivity aluminum nitride ceramic substrate prepared by the preparation method as claimed in claim 6 or 7.

9. The high-strength, high-thermal-conductivity aluminum nitride ceramic substrate as claimed in claim 8, characterized in that: The aluminum nitride ceramic substrate has a bending strength of not less than 402.3 MPa, a thermal conductivity of not less than 112.2 W / m·K, and a fracture toughness of not less than 3.19 MPa·m 1 / 2 .

10. Use of the aluminum nitride ceramic substrate as claimed in claim 8 or 9 as a packaging material in a power semiconductor device.

Citation Information

Cited By

  • Method for preparing high-thermal-conductivity aluminum nitride ceramic by graphite-induced liquid-phase oriented migration

    CN121948977A

  • Method and device for continuously preparing aluminum nitride whiskers

    CN122543165A

  • Three-dimensional high-thermal-conductivity aluminum nitride ceramic fiber with controllable morphology and high purity and a preparation method thereof

    CN122791510A

  • Composite ceramic substrate, composition for preparing same, preparation method therefor, and use thereof

    WO2026179397A1